Notes on the spider genus Lathys Simon, 1884 (Araneae: Dictynidae), with description of four new species from China - Zhang, Zhi-Sheng; Hu, Dong-Sheng; Zhang, Yao-Guang (Zootaxa, 2012)
Four Lathys species of the family Dictynidae have been previously recorded from China. Our study showed that they wereeither wrongly placed or misidentified. In this paper, four new Lathys species are described: L. borealis sp. nov. (male, female),L. spiralis sp. nov. (female) L. subalberta sp. nov. (male, female) and L. subhumilis sp. nov. (male, female). Photos of the North American species L. alberta Gertsch, 1946 are provided for comparison purposes.